A Comparison of In-person, Telephone, and Secure Messaging for Type 2 Diabetes Self-Management Support. (July 2014) - Greenwood, Deborah A.; Hankins, Andrea I.; Parise, Carol A.; Spier, Valerie; Olveda, Joan; Buss, Kimberly A.
Ongoing interaction between diabetes educators and patients is necessary for making and sustaining behavior changes essential for glycemic control and subsequently reducing the complications of diabetes. Purpose: The purpose of this study was to determine the feasibility of diabetes self-management support (DSMS) delivered via telephone or secure message and to compare clinical outcomes (A1C, LDL), behavioral goal achievement, and health maintenance task completion. Methods: In sum, 150 persons with type 2 diabetes who completed diabetes self-management education self-selected DSMS methods: 1 in-person visit (n = 47), 3 brief visits by phone (n = 44), or 3 by secure message (n = 59) through electronic health record. DSMS included evaluation of goal achievement, barriers and facilitators, problem solving, and review of health maintenance exams. Self-reported data were collected at 9 months. Results: There were no significant differences among groups in main outcomes between baseline and 9-month follow-up. Behavioral goals were achieved by 59% of in-person participants, 73% phone, and 77% secure message. Sixty-two completed the intervention per protocol: fewer online than in-person or phone groups. Mean attempts to contact participants was significantly greater in the secure message group. Phone contact was significantly longer than secure message. Conclusions: Telephone and secure message was feasible for providing DSMS. Three brief contacts by phone or secure message resulted in similar outcomes when compared to an in-person visit. Secure messaging required less staff time, but increased patient engagement is needed.